Avoiding the weaknesses of a penetration test. Issue 4 (April 2019) - Baiardi, Fabrizio
Abstract : A penetration test is a traditional solution for evaluating and improving the robustness of an ICT system. Such tests can be comprehensive, but problems can arise when deciding how to use its results to select the countermeasures against a successful penetration. These problems may explain the successful attacks against systems that previously passed such tests. So, it's useful to look at some theoretical explanations of the weaknesses of a penetration test and suggest some alternatives.